2001
DOI: 10.1046/j.1365-2109.2001.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three dietary oils on disease susceptibility in Arctic charr (Salvelinus alpinusL.) during cohabitant challenge withAeromonas salmonicidassp.salmonicida

Abstract: Arctic charr (Salvelinus alpinus L.) were fed diets based on a commercial recipe supplemented with either linseed, soybean or marine oil prior to cohabitant challenge with Aeromonas salmonicida ssp. salmonicida. Mortality varied significantly between the three dietary groups. Highest mortality (48%) was observed in fish fed the marine oil and the lowest mortality (20%) was in the group fed soybean oil. Transmission electron microscopy (TEM) examination of the digestive tract of uninfected fish demonstrated sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 42 publications
1
65
1
1
Order By: Relevance
“…In a long-term feeding study using SBO and FOs, Waagbø et al (1993) showed that Atlantic salmon fed high levels of FOs had better survival when infected with Aeromonas salmonicida (the causative agent of furunculosis), despite the fact that head kidney macrophage phagocytosis and bacterial killing was reduced in these fish (IL-1 and serum hemolytic activity was unaffected). In contrast to these results, Gjøen et al (2004) reported no differences in Atlantic salmon susceptibility to infection by A. salmonicida, while Lødemel et al (2001) reported that Arctic charr fed diets supplemented with SBO and challenged with A. salmonicida showed elevated survivability compared to fish fed a FO based diet (SBO = 20% mortality vs FO = 48% mortality).…”
Section: Soybean Oilcontrasting
confidence: 46%
“…In a long-term feeding study using SBO and FOs, Waagbø et al (1993) showed that Atlantic salmon fed high levels of FOs had better survival when infected with Aeromonas salmonicida (the causative agent of furunculosis), despite the fact that head kidney macrophage phagocytosis and bacterial killing was reduced in these fish (IL-1 and serum hemolytic activity was unaffected). In contrast to these results, Gjøen et al (2004) reported no differences in Atlantic salmon susceptibility to infection by A. salmonicida, while Lødemel et al (2001) reported that Arctic charr fed diets supplemented with SBO and challenged with A. salmonicida showed elevated survivability compared to fish fed a FO based diet (SBO = 20% mortality vs FO = 48% mortality).…”
Section: Soybean Oilcontrasting
confidence: 46%
“…These differences generally seem to disappear at lower temperatures, suggesting an additional temperaturedependent role of n-3 HUFA. Furthermore, in Arctic charr fed diets supplemented with soybean oil or fish oil and challenged with Aeromaonas salmonicida (the causative agent of furunculosis), increased mortality (48%) was observed in the fish oil group, compared to the soybean oil group (20%) (Lødemel et al 2001). One group of fish supplemented with a linseed oil diet was intermediate between the two.…”
Section: Effect Of the Oil Fraction On Immunitymentioning
confidence: 98%
“…Manjili et al (1998) showed that hyperplasic goblet cell and changes in the composition of goblet cell mucins follow primary infection of guinea pigs with Trichostrongylus colubriformis. In fish, an excess of secreted mucus is generally described when both intestinal and gill epithelia interact with microrganisms (Ferguson et al 1992, Guzman-Murillo et al 2000, Lodemel et al 2001, Kruatrachue et al 2003, and with intestinal helminths (George & Nadakal 1978, AdelMeguid et al 1995.…”
Section: Discussionmentioning
confidence: 99%